Kajian Eksperimental Sifat Mekanik Beton Porous dengan Variasi Faktor Air Semen - Desmaliana, Erma; Hazairin, Hazairin; Herbudiman, Bernardinus; Lesmana, Rossa (Jurnal Teknik Sipil, 2018)
Abstract: Porous concrete is one of the sustainable concrete technology innovations without fine aggregates and high porosity. Porous concrete could be used on road pavement to overcome the run-off water and applied as a retaining wall to minimize groundwater pressure. This study purposes to determine the mechanical properties of compressive strength, split-tensile strength, flexuralstrength and permeability of porous concrete with various water cement ratio experimentally. 10-mm-diameter and 20-mm-diameter of Batujajar split used as coarse aggregates. This study uses concrete mixture with water cement ratio variations of 0.3, 0.35, 0.4, 0.45 and 0.5 on the coarse aggregate gradation of continuous. The test specimens used three cylinders of 15x30cm for compressive and split-tensile strengths, except for permeability strength which used one cylinder of 10x20cm. Beam specimens of 15x15x60cm were used for bending strength test by third-point loading method. The tested mechanical properties are 7, 14 and 28 days compressive strengths, 28 days split-tensile strength, 28 days bending strength and 28 days permeability strength. The experimental results show that the average compressive strengths of porous concrete with variationof water cement ratio of 0.3, 0.35, 0.4, 0.45 and 0.5 for 28 days is 17.9 MPa, 16.1 MPa, 14.2 MPa, 11.2 MPa and 8.8 MPa, respectively. The average split-tensile strengths of porous concrete with variation of water cement ratio of 0.3, 0.35, 0.4, 0.45 and 0.5 for 28 days is 1.6 MPa, 1.5 MPa, 1.4 MPa, 1.2 MPa and 0.9 MPa, respectively. The average flexural strengths of porous concrete with variation of water cement ratio of 0.3, 0.35, and 0.4 for 28 days is 1.6 MPa, 1.5 MPa and 1.1 MPa, respectively. The average permeability strengths of porous concrete with variation of water cement ratio of 0.3, 0.35, 0.4, 0.45 and 0.5 for 28 days is 3.5 mm/s, 3.7 mm/s, 4.1 mm/s, 4.3 mm/s dan 5.0 mm/s, respectively. Based on the experimental study it shows that porous concrete with all variations of water cement ratio achieves the structural strength and is recommended as a pre-fabricated pavement structure material with small dimensions relatively to prevent bending cracks.Â Abstrak: Beton porous merupakan salah satu inovasi teknologi beton berkelanjutan tanpa agregat halus dengan porositas tinggi. Beton porous ini dapat digunakan pada perkerasan jalan untuk menanggulangi air run-off, serta dapat diaplikasikan sebagai dinding penahan tanah yang berfungsi untuk meminimalisir tekanan air tanah. Penelitian ini bermaksud untuk mengkaji secara eksperimental sifat mekanis terhadap kuat tekan, kuat tarik belah, kuat lentur dan permeabilitas beton porous dengan berbagai variasi faktor air semen. Agregat kasar yang digunakan batu pecah Batujajar berukuran 10 mm â€“ 20 mm. Penelitian ini menggunakan campuran beton dengan variasi faktor air semen sebesar 0.3, 0.35, 0.4, 0.45, dan 0.5 pada gradasi agregat kasar menerus. Benda uji yang digunakan untuk setiap varian adalah 3 benda uji beton silinder yang berukuran 15x30 cm untuk uji kuat tekan beton dan uji kuat tarik belah beton dan 1 benda uji beton silinder 10x20 cm untuk uji permeabilitas. Benda uji balok berukuran 15x15x60 cm untuk uji kuat lentur dengan metode third point loading. Sifat mekanik yang diuji adalah kuat tekan beton pada umur 7, 14 dan 28 hari untuk uji kuat tekan beton dan 28 hari untuk kuat tarik belah beton, kuat lentur beton dan permeabilitas. Hasil eksperimen menunjukkan nilai kuat tekan beron porous dengan varian campuran faktor air semen 0.3, 0.35, 0.4, 0.45, 0.5 untuk 28 hari berturut-turut adalah 17.9 MPa, 16.1 MPa, 14.2 MPa, 11.2 MPa, dan 8.8 MPa. Nilai kuat tarik belah beton dengan varian campuran faktor air semen 0.3, 0.35, 0.4, 0.45, 0.5 untuk 28 hari berturut-turut adalah 1.6 MPa, 1.5 MPa, 1.4 MPa, 1.2 MPa, dan 0.9 MPa. Nilai kuat lentur beton dengan varian campuran faktor air semen 0.3, 0.35, 0.4 untuk 28 hari berturut-turut adalah 1.6 MPa, 1.5 MPa, 1.1 MPa. Nilaipermeabilitas beton porous dengan varian campuran faktor air semen 0.3, 0.35, 0.4, 0.45, 0.5 adalah 3.5 mm/det, 3.7 mm/det, 4.1 mm/det, 4.3 mm/det dan 5.0 mm/det. Dari hasil eksperimen menunjukkan bahwa beton porous dengan semua variasi faktor air semen mampu mencapai kekuatan struktural dan penggunaannya layak direkomendasikan sebagai material struktur perkerasan pre-fabrikasi dengan dimensi yang relatif kecil untuk menghindari retak lentur.